An exploration of how Grade 3 Foundation Phase teachers develop basic scientific process skills using an inquiry-based approach in their classrooms - Nhase, Zukiswa (Rhodes University, Faculty of Education, Department of Education, 2020)
Some studies have looked at Foundation Phase teachers' perspectives on the teaching of science in this phase. Such studies have highlighted various challenges on the teaching of science in the Foundation Phase. They pointed out issues such as large class numbers, lack of resources and lack of science knowledge from Foundation Phase teachers. However, none of these studies have looked at how Foundation Phase teachers are using an Inquiry-Based Approach in their classrooms instead few studies have looked at the Foundation Phase teachers' perspectives about scientific inquiry in this phase. Even though many scholars have presented several challenges to the teaching of science both at secondary and primary level, the argument is strongly made that Foundation Phase learners should be exposed to the learning of science. Generally, children at the Foundation Phase level naturally enjoy observing and thinking about nature; exposing learners to science develops positive attitudes towards science; the use of scientifically informed language at an early age influences the eventual development of scientific concepts; children can understand scientific concepts and reason scientifically; and science is an efficient means for developing scientific thinking. It is within these arguments and discussions that this interpretive case study research sought to explore the Pedagogical Content Knowledge of four Foundation Phase teachers in developing the Scientific Process Skills using an Inquiry-Based Approach in their classrooms and subsequently, the significance of this research study. The socio-cultural theory, Topic Specific Pedagogical Content Knowledge, Zaretskii's six conditions for development during mediation and the principles of an Inquiry-Based Approach were used as analytical lenses in this research. To use an Inquiry-Based Approach, generally teachers have to understand its principles and know how to develop basic Scientific Process Skills while teaching the science content. In the Foundation Phase, the Natural Sciences component or content is embedded in the Beginning Knowledge study area of the Life Skills subject and this can create difficulties for teachers to even recognise the scientific concepts in the Life Skills. The four IsiXhosa female teachers used the home language of learners as the language of instruction to implement an Inquiry-Based Approach in their classrooms. Data were generated in four phases. Phase one was baseline data through document analysis. Three of the phases were directed by the research question asked. Data were generated using questionnaires, interviews (semi-structured and stimulated recall), lesson observations (videotaped) and group reflections and discussions. From the work of Vygotsky, Zaretskii formulated six conditions that can be used to develop learners' zone of proximal development in learning and these were used as analytical lenses to analyse data to understand how teachers mediated learning and development of Scientific Inquiry in their Grade 3 classrooms. In addition, the principles of an Inquiry-Based Approach were used as analytical lenses as to how teachers implemented the scientific inquiry approach. The categories or components of Topic Specific Pedagogical Content Knowledge were used as analytical lenses as to how these teachers dealt with science concepts or content when using an inquiry-based Approach in their classrooms. Using the home language of learners as an instructional tool, data showed that learners were afforded the opportunity to freely engage in activities and as a result, the context of learning was non-threatening for both teachers and learners. Although learning activities could be improved, teachers created social spaces for learners to take part in learning. In addition, the use of learners' environments in the observed lessons made it comfortable for learners to act as young scientists. The new knowledge in this research was presented by the use of the adapted analytical tool, which combined diverse components of theory and literature that aligned with each other. The reflection space for the participants did not only afford the participants to discuss about each other's lessons or experiences in this research, it allowed the participants to engage with the research objectives. The reflection space strengthened the research ethics if this study. Hence, the concept that says, 'Absenting the absences'. In conclusion, the study thus recommends further professional development spaces that promote community of practice in using an Inquiry-Based Approach in the Foundation Phase.
Keywords: Elementary school teaching-- -- South Africa; Elementary school teachers -- South Africa; Elementary school teachers -- In-service training -- South Africa; Science -- Study and teaching (Elementary) -- South Africa; Learning, Psychology of; Cognition in children; Inquiry-based learning -- South Africa; Active learning -- South Africa; Pedagogical content knowledge -- South Africa; Educational change -- South Africa; Socio-cultural theory